The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/pd.5433
|View full text |Cite
|
Sign up to set email alerts
|

Spina bifida screening in the first trimester using ultrasound biparietal diameter measurement adjusted for crown‐rump length or abdominal circumference

Abstract: Objective Compare the performance of first trimester ultrasound biparietal diameter (BPD) screening for open spina bifida (OSB) when BPD is adjusted for crown‐rump length (CRL) or abdominal circumference (AC). Methods For 63 OSB and 24 265 unaffected pregnancies, BPD was expressed as multiple of the normal median (MoM) based on CRL and on AC, and as the ratio BPD/AC. Screening performance was assessed by the Mahalanobis distance, the observed detection rate with normal fifth and 10th percentile cut‐offs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…This strengthens previous findings about the influence of fetal lateral ventricle size before surgery on postnatal shunt rates and reinforces the notion that there is no reason to delay fetal surgery . Currently, accurate screening of an OSD is possible at the 11 to 13 +6 week anomaly scan, allowing for better planning for the early treatment or, in some cases, termination of the pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…This strengthens previous findings about the influence of fetal lateral ventricle size before surgery on postnatal shunt rates and reinforces the notion that there is no reason to delay fetal surgery . Currently, accurate screening of an OSD is possible at the 11 to 13 +6 week anomaly scan, allowing for better planning for the early treatment or, in some cases, termination of the pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, only few data have been published on OSB ultrasound markers in the axial plane of the head. Some groups focused on the small head size [12][13][14]17 , relative either to CRL or to abdominal size 14,27 . Other studies reported on changes at the level of the cerebral peduncles 28 , which become parallel and posteriorly shifted, resulting in compression of the aqueduct of Sylvius 10,15,16,19,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The DR of 66.7% for BPD < 5th percentile was marginally superior to that previously reported. In previous studies, the DR for this marker ranged from 26% to 55.6% . The use of BPD/AC ratio marginally improved the detection of open spina bifida, identifying 70.4% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The use of BPD/AC ratio marginally improved the detection of open spina bifida, identifying 70.4% of the cases. DRs of 54% using BPD/AC and 69.2% using BPD/transverse abdominal diameter < 1 have been reported …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation